Cross-generational effect of prenatal morphine exposure on neurobehavioral development of rat pups - Slamberová, R; Riley, M A; Vathy, I (Physiological research, 2005)
Prenatal exposure to opiates can have devastating effects on the development of human fetuses and may induce long-term physical and neurobehavioral changes during postnatal maturation. The present study was aimed at identifying cross-generational effects of prenatal morphine exposure in Sprague-Dawley rats. Pregnant rats were injected subcutaneously with either saline or morphine (10 mg/kg) twice daily during gestational days 11-18. Litter size, percentage of males and females, anogenital distances (AGDs), righting reflex, and body weight were assessed in prenatally morphine-exposed pups (first generation) and their offspring (second generation). Both prenatally morphine-exposed pups and offspring of prenatally morphine-exposed dams exhibited an increased latency to right. Additionally, second generation pups were slower in righting than first generation pups. During the early postnatal period the second generation pups weighed less than the first generation regardless of drug exposure. The AGDs of second generation male pups were decreased relative to the first generation. Our data provide important novel information about the trans-generational effects of maternal opiate abuse that may be useful for understanding/evaluating the teratogenic effects of prenatal opiate exposure.
Keywords: gestační stáří; Animals; novorozená zvířata; Female; Morphine; Analgesics, Opioid; matka - expozice noxám; Gestational Age; ženské pohlaví; Maternal Exposure; Animals, Newborn; chování zvířat; těhotenství; zpožděný efekt prenatální expozice; Rats, Sprague-Dawley; Central Nervous System; opioidní analgetika; Male; maternofetální výměna látek; potkani Sprague-Dawley; Maternal-Fetal Exchange; Prenatal Exposure Delayed Effects; krysa rodu Rattus; Behavior, Animal; morfin; zvířata; centrální nervový systém; mužské pohlaví; Pregnancy; Rats